Scaling of the Thermally Induced Sign Inversion of Longitudinal Spin Seebeck Effect in a Compensated Ferrimagnet: Role of Magnetic Anisotropy. (12th November 2021) - Chanda, Amit; Holzmann, Christian; Schulz, Noah; Seyd, Johannes; Albrecht, Manfred; Phan, Manh‐Huong; Srikanth, Hari
Abstract: The authors report on a systematic investigation of the longitudinal spin Seebeck effect (LSSE) in a GGG(Gd3 Ga5 O12 )/GdIG(Gd3 Fe5 O12 )/Pt film series exhibiting an in‐plane magnetic easy axis with a compensation temperature ( T Comp ) that decreases from 270 to 220 K when decreasing GdIG film thickness from 272 to 31 nm, respectively. For all the films, the LSSE signal flips its sign below T Comp . The authors demonstrate a universal scaling behavior of the temperature dependence of LSSE signal for the GdIG films around their respective T Comp . Additionally, the authors demonstrate LSSE in a 31 nm GdIG film grown on a lattice‐mismatched GSGG (Gd3 Sc2 Ga3 O12 ) substrate that exhibits an out‐of‐plane magnetic easy axis at room temperature. However, this sample reveals a spin reorientation transition where the magnetic easy axis changes its orientation to in‐plane at low temperatures. A clear distinction is observed in the LSSE signal for the GSGG/GdIG(31 nm)/Pt heterostructure, relative to GGG/GdIG(31 nm)/Pt showing an in‐plane magnetic easy axis. The findings underscore a strong correlation between the LSSE signal and the orientation of magnetic easy axis in compensated ferrimagnets and opens the possibility to tune LSSE through effective anisotropy. Abstract : Gd3 Fe5 O12 (GdIG) is a compensated ferrimagnetic insulator. It is demonstrated that the thermospin‐voltage across the GGG/GdIG/Pt heterostructures with different GdIG thicknesses and hence, different compensation temperatures ( T Comp ) fall onto a single master curve around their respective T Comp . Such universal behavior will be helpful to fabricate novel spincaloritronic devices wherein the thermospin‐voltage can be switched by appropriately tailoring the operational temperature.